2008
DOI: 10.2224/sbp.2008.36.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Racial Representation in Children’s Television Programming in Kuwait: Implications for Education

Abstract: An examination was carried out of television programs made for children and also television programs that involved children, regardless of their intended audience. The aim of the study was to determine the effects of these programs in terms of gender and race representations and stereotypes. A content analysis was run on segments from two television channels, the Kuwait national channel and the Egyptian satellite channel. Findings are given and discussed against a rich background of research in this area, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Consistent with previous findings (e.g., Al-Shehab, 2008;Kalliny et al, 2008), differences in gender portrayals were found between the Arab countries producing the programs. Using the liberal-conservative continuum for Arab countries proposed by Kalliny and his colleagues (2008), conservative countries (Kuwait and Saudi Arabia) had more female characters in female stereotypical roles than the more liberal Arab countries (Syria, Lebanon, and Egypt).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with previous findings (e.g., Al-Shehab, 2008;Kalliny et al, 2008), differences in gender portrayals were found between the Arab countries producing the programs. Using the liberal-conservative continuum for Arab countries proposed by Kalliny and his colleagues (2008), conservative countries (Kuwait and Saudi Arabia) had more female characters in female stereotypical roles than the more liberal Arab countries (Syria, Lebanon, and Egypt).…”
Section: Discussionsupporting
confidence: 91%
“…The present study examines differences in gender portrayals between the different producing countries. Based on previous findings (Al-Shehab, 2008;Kalliny et al, 2008) we hypothesize that programs produced in the more conservative gulf countries (e.g., Saudi Arabia and Kuwait) show more stereotypical portrayals of women than programs produced by the more liberal Levant countries (e.g., Lebanon and Syria).…”
Section: Transnational Arab Television Contentmentioning
confidence: 85%
See 2 more Smart Citations
“…Reducing the presence of females in certain roles or restricting their presence to other roles is a worrying trend. Additionally, the placement of only male characters in powerful and influential roles could result in a young child developing a warped view of gender rolesa development that could then result in serious consequences in later life (Shehab, 2008). It is, therefore, worrying that many kids' programmes today lack strong female characters.…”
Section: Social Reality Versus Television Depictionsmentioning
confidence: 99%